Analisis Penerapan Lean Manufacturing Pada Penurunan Cacat Feed Roll Menggunakan Metode PDCA (Studi Kasus PT. XYZ) - Azwir, Hery Hamdi; Setyanto, Agus Kurniawan (Jurnal Rekayasa Sistem Industri, 2017)
PT XYZ is a company that produce tools, machine parts, and special purpose machines. Based on data from the production department, there are some products with high defect and then need rework. This condition would be very harmful because it will increase the cost that should not be necessary. The research is to find the cause of the occurrence of this defect and then fix it. From the observation result showed that the production of feed roll component has a high defect rate which is 70.59% must be reworked, based on the data during January - September 2016. In October - December 2016 the improvement effort was done by using lean manufacturing approach and PDCA. The results of this improvement provide improved quality of the feed roll component so that the rework gradually decreases and eventually does not exist. Then the cost of production before the repair of Rp 668,694, - reduced to Rp 413,983, -. There was a significant decrease in production cost by 38%.